Sjogren’s syndrome presenting with recurrent hypokalemic paralysis - Chauhan, Parikshit Singh; Singh, Samarjeet; Sangwan, Harwinder (Indian Journal of Case Reports, 2018)
Sjogren’s syndrome is an autoimmune disorder commonly affecting females and presents with the dryness of the mouth and eyes. Here, we present an interesting case of Sjogren’s syndrome, initial presentation with distal renal tubular acidosis (RTA) causing recurrent hypokalemic paralysis, and dyspnea requiring ventilator support. The patient improved dramatically with potassium and alkali supplementation. She has been on follow-up for the past 3 months and remains asymptomatic. Only a few case reports and series have been reported on such initial presentation of Sjogren’s syndrome. To conclude, one must be aware of distal RTAs associated with autoimmune disorder presenting with hypokalemic paralysis.